2016
DOI: 10.1016/j.margeo.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of bottom trawl fishing damage to ancient shipwreck sites

Abstract: Bottom trawl fishing presents a severe yet largely unquantified threat to shipwreck sites. Here we present a quantification of damage to sites from the Aegean and Black seas through high resolution imaging of 45 shipwrecks discovered by the E/V Nautilus expeditions, 2009-2012. These shipwrecks are part of a modern submarine landscape that is heavily damaged by trawls, which also remove sediment and smooth out natural features of the seabed. We quantify the severity of this threat to archaeological sites throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…
Bottom trawl fishing is among the most destructive anthropogenic pressures acting on benthic ecosystems, but the full extent of the damage is undocumented because of the limited number of deep-sea observations of impacted regions (e.g., Brennan et al, 2012Brennan et al, , 2016. As part of its continuing ocean exploration mission, in 2011, E/V Nautilus conducted a remotely operated vehicle (ROV) survey along a transect in a submarine canyon in the Mediterranean's Alboran Sea off southern Spain at depths ranging from 1,200 m to <300 m .
…”
mentioning
confidence: 99%
“…
Bottom trawl fishing is among the most destructive anthropogenic pressures acting on benthic ecosystems, but the full extent of the damage is undocumented because of the limited number of deep-sea observations of impacted regions (e.g., Brennan et al, 2012Brennan et al, , 2016. As part of its continuing ocean exploration mission, in 2011, E/V Nautilus conducted a remotely operated vehicle (ROV) survey along a transect in a submarine canyon in the Mediterranean's Alboran Sea off southern Spain at depths ranging from 1,200 m to <300 m .
…”
mentioning
confidence: 99%
“…Research has shown that those ancient wrecks that lie within the trawling exclusion zone are mostly or fully intact, whereas those lying outside the limit have suffered significant damage from trawls (Brennan et al ., : 64–67; Krumholz and Brennan, : 130; Brennan et al ., : 84). In addition, the better‐preserved wrecks, serving as artificial reef habitats, demonstrated more abundant fish populations and biodiversity compared to those degraded by trawling (Krumholz and Brennan, : 131–132; Brennan et al ., : 87). With these data, a strong case can be made that the creation of marine protected areas with a high concentration of shipwrecks can result in both improved protection of maritime cultural sites and an increase in fish population in adjacent fishing grounds through adult fish spillover.…”
Section: Discussionmentioning
confidence: 99%
“…These showed that the site changed significantly, with >95% of the artefacts moved, including a conspicuous notched timber now missing. Calculations from comparing the two survey data sets indicated that more than 15m 3 of material was removed from the site between visits (Brennan et al ., : 83–87).…”
Section: Expedition Background and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bottom trawling has destructive effects on priority habitats (e.g., coral community, coralligenous formations, seagrass beds) which are targets for conservation actions [12][13][14]. In addition, marine geoarchaeological sites have also been heavily impacted by trawl-fishing [15,16]. The amount of the damage done depends on the spatial extent and the frequency of trawling [17].…”
Section: Introductionmentioning
confidence: 99%